2006
DOI: 10.1359/jbmr.060107
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Apoptosis Is Induced by Weightlessness in Mice and Precedes Osteoclast Recruitment and Bone Loss

Abstract: Mechanical stimulation of cultured osteocytic cells attenuates their apoptosis. We report here that, conversely, reduced mechanical forces in the murine model of unloading by tail suspension increases the prevalence of osteocyte apoptosis, followed by bone resorption and loss of mineral and strength.Introduction: Mechanical loading is critical for the maintenance of bone mass; weightlessness, as with reduced physical activity in old age, bed rest, or space flight, invariably leads to bone loss. However, the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
308
2
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(336 citation statements)
references
References 59 publications
12
308
2
14
Order By: Relevance
“…However, we did not detect any changes in osteocyte number or apoptosis in the conditional knock mice as measured by TUNEL staining, osteocyte density, or osteocyte-specific gene expression. Moreover, since osteocyte apoptosis has been associated with (40), or shown to cause (41-43), increased oste- oclast formation and bone resorption, an increase in osteocyte apoptosis would not explain the reduced osteoclast formation in mice lacking autophagy in osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not detect any changes in osteocyte number or apoptosis in the conditional knock mice as measured by TUNEL staining, osteocyte density, or osteocyte-specific gene expression. Moreover, since osteocyte apoptosis has been associated with (40), or shown to cause (41-43), increased oste- oclast formation and bone resorption, an increase in osteocyte apoptosis would not explain the reduced osteoclast formation in mice lacking autophagy in osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for how PTH could explain the cortical bone remodeling observed in the current study is shown in Figure 6. Intact PTH (PTH 1-84), acting through the PTH1 receptor on osteocytes and osteoblasts, could prevent the increased apoptosis and decreased bone formation rates normally associated with disuse [3,52,53]. Prevention of osteocyte apoptosis would prevent increases in targeted remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphometric analysis was performed using OsteoMeasure high-resolution digital video system (OsteoMetrics, Decatur, GA, USA) interfaced to an Olympus BX51 fluorescence microscope (Olympus America Inc., Center Valley, PA, USA). (39) Osteoclasts were quantified on lumbar vertebra L 2 thin sections stained for tartrate-resistant acid phosphatase (TRAP) and counterstained with Toluidine Blue as published. (34,37) An osteoclast was defined as a TRAPpositive cell attached to the bone surface with more than one nucleus.…”
Section: Quantitative Pcrmentioning
confidence: 99%